The Impact of Pocket Money on Student Learning Outcomes at SMP Budi Satrya Medan Tembung - Attahira Lutfiah Azmi (Yayasan Bayt Shufiya Nusantara, 2024)
This study aims to analyze the influence of pocket money on student learning outcomes at Budi Satrya Junior High School Medan Tembung. The method used is a quantitative approach with primary data collection through the distribution of questionnaires to 100 student respondents who were randomly selected. The collected data was analyzed using SPSS, with validity, reliability, and determination tests. The results of the study showed that the provision of allowances had a significant effect on the learning concentration of students with a t-count value of 1,820 which was greater than the t-table of 1,676. The determination test showed that the influence of pocket money on student learning outcomes was 11.8%. This research provides important insights into the importance of providing adequate allowances to support students' academic achievement.